Role of Mass Media to Prevent Child Labour - Balamurugan, J (Journal of Advanced Research in Journalism & Mass Communication, 2019)
Child Labour is a social evil that has been persisting in the Indian the social order for a very long time. Children under the age of 14 are employed to work under hazardous conditions in various industries and businesses. Firstly, this research paper deals with the involvement and role of the Mass Media on abolishing child labour across India. Secondly, it is to see whether the role of the Mass Media has reached the people of small cities like Vellore in India. Finally, to see how the Government and various NGO’s use Mass Media to reach as many as they can, regarding this social evil in India. How to cite this article: Balamurugan J. The Role of Mass Media in the Prevention of the Child Labour Problem in Vellore, India. J Adv Res Jrnl Mass Comm 2019; 6(2): 18-22.